Innovation and bioethics in surgery: Redefining boundaries for a safe and human-centered future - Evelyn Frias-Toral; Alex Enrique Vásconez-García; Melannie Toral-Noristz; Martín Campuzano-Donoso; Ana Karina Zambrano; Claudia Reytor-González; Daniel Simancas-Racines (Medwave)
Since surgery is a complex procedure due to multiple factors, it is more difficult to rigorously evaluate innovative processes in this field than clinical trials of new drugs. Being able to carry out an adequate study design with all its corresponding implications, achieving high-quality standards for these studies, ensuring respect for patients' rights, and verifying that their principles of beneficence, minimization of the risk of harm, justice and autonomy are a challenge for many researchers and professionals involved in the surgical process. Hence, it is advantageous to have guides that guarantee the methodological quality of research on innovative surgical procedures and that these guides include the ethical aspects involved in each of their stages. This review aims to make a historical overview of what has been published on the ethical approach to surgical innovation. In addition, the ethical aspects of the stages of the IDEAL framework for surgical innovation will be explained.